LEVELS OF OVERWEIGHT AND OBESITY IN CHILDREN AND ADOLESCENTS NETWORK OF MUNICIPAL PUBLIC EDUCATION-AL ARAPIRACA (Fiep Bulletin - online, 2012)
The objective was to identify the levels of overweight and obesity in children and adolescents from public schools in municipal Arapiraca-AL. The transversal study had a sample of 1634 schoolchildren of both sexes enrolled in 2010. We collected values ??for the total body mass and height (to calculate body mass index - BMI), waist circumference as well as anatomical. We used the statistic of central tendency. For both genders the results pointed to a profile within normal limits for both BMI and waist circumference for anatomical. However, when analyzed by gender, levels of excess weight (overweight and obesity) were 19.92% for females and 17.16% for males. As for the waist anatomical results pointed to a profile within normal limits. It is concluded that the students of both genders had normal levels of BMI and waist circumference, but by gender, females had higher levels of overweight corroborating with the literature.
Keywords: Overweight; Obesity; Children; Adolescents.